Curriculum studies and the history of the present - Popkewitz, Thomas S. (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
The field of curriculum history, as the broader education history, is organized by traditions of intellectual and social history; the former is concerned with the organization and changes in ideas and the latter with ideas as representing institutional and social changes found in policy and the actual programmatic developments. This paper takes a approach to curriculum as a history of the present. Is considered curriculum as ‘converting ordinances’, thinking of curriculum as narratives of national belonging and science coupled with salvation themes that generate cultural theses about modes of living. The second section discusses American Progressive Education in a cross Atlantic Protestant reformism concerned with the Social Question. The final section explores the cultural theses generated in the formation of mathematics, literacy, and music curriculum.